Preparation method of silicon dioxide aerogel felt
By steam drying in a steam dryer, the problems of long drying time, low mechanical strength and high production cost in the prior art are solved, and the preparation of aerogel felt with excellent thermal insulation performance is achieved.
Patent Information
- Application Number
- CN202380053371.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, when preparing silica aerogel felt, there are problems such as long drying time, low mechanical strength, high production cost and reduced thermal insulation performance.
Silica aerogel felts are prepared by steam drying, and dried by supplying steam in a steam dryer. The drying temperature is greater than 70°C, the flow rate is between 0.1 and 25 kg/h, and the drying time is between 30 minutes and 2 hours.
Effective drying in a short time is achieved, and silica aerogel felts with excellent thermal insulation properties are prepared, reducing production costs and simplifying equipment conditions.
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0107778 filed on August 26, 2022 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present invention relates to a method for preparing a silica aerogel felt comprising a steam drying step. Background Art
[0004] Aerogel is a highly porous material composed of nanoparticles and has high porosity, large specific surface area and low thermal conductivity, and is therefore considered a preferred choice for highly efficient thermal insulation materials, sound insulation materials, etc. However, the fact that such aerogel has very low mechanical strength due to its porous structure has led to the ongoing work on developing aerogel composites, in which aerogel is bonded to a fiber mat formed of typical thermal insulation fibers (e.g., organic or inorganic fibers) by impregnation.
[0005] For example, a silica aerogel-containing felt using silica aerogel is prepared by a process of silica sol preparation-gelation-aging-surface modification-drying. In this case, when aging and surface modification steps are included, a large amount of solvent is required, and a large amount of waste liquid generated after preparation requires separate treatment costs.
[0006] Furthermore, typical methods for preparing aerogels have challenging issues such as complicated overall process steps, long process time, and high production costs for commercialization involving large-scale production due to additional equipment and a large space for aging and surface modification, making commercialization challenging despite excellent thermal insulation performance compared to typical thermal insulation materials.
[0007] For aerogel felt, atmospheric hot air drying (hot air drying) is usually mainly used, but hot air drying heats and dries the sample sequentially from the outside to the inside, so that the high volatility organic solvent evaporates before the low volatility water. Therefore, drying is carried out with an increased amount of water in the pores of the gel, which often leads to capillary phenomena that destroy the pore structure due to shrinkage, etc. Aerogel felt with failed pore structure has the problem of relatively reduced insulation performance. This may be further troublesome when drying is carried out immediately without replacing with an organic solvent with low surface tension.
[0008] In addition, hot air drying takes a relatively long time to raise the temperature of the drying sample to the optimal drying temperature, and is therefore performed at a temperature lower than the optimal drying temperature, thereby reducing the drying efficiency when the aerogel felt is dried only by hot air drying. In addition, there is also the risk of oil mist explosion.
[0009] Supercritical drying has been proposed as a method to overcome the low drying efficiency and reduced insulation performance of hot air drying. Supercritical drying is a drying method in which a supercritical fluid such as supercritical CO2 is added to a high-pressure reactor and replaced with ethanol in a wet gel felt, and the replaced ethanol is extracted. However, the problem is that supercritical drying requires a separate drying device for supercritical extraction, resulting in a very high initial investment cost. In addition, supercritical drying must undergo a compression-extraction-decompression process, and this is time-consuming. In particular, the extraction step in supercritical drying works based on the following principle: a liquid fluid that is not in a supercritical state dilutes and removes a solvent in the initial stage, wherein the solvent is present in a larger proportion than the supercritical fluid, and therefore, with a larger proportion of the solvent, the extraction takes significantly longer time. In addition, drying is carried out in a supercritical extractor, so a continuous drying process is not applicable, and only an intermittent process is allowed. Therefore, when supercritical drying is applied alone from a drying process, commercialization / large-scale production of aerogel felt can hardly be achieved.
[0010] [Related prior art documents]
[0011] [Patent document]
[0012] (Patent Document 1) Korean Patent Publication No. 2001-0033498 (published on April 25, 2001). Summary of the invention
[0013] Technical issues
[0014] One aspect of the present invention provides a method for preparing a silica aerogel felt having excellent thermal insulation properties by effectively drying in a short time.
[0015] Technical Solution
[0016] According to one aspect of the present invention, there is provided a method for preparing a silica aerogel felt, the method comprising the following steps:
[0017] 1) preparing a silica sol containing a silica precursor composition;
[0018] 2) impregnating a felt substrate with the silica sol;
[0019] 3) while the felt substrate is impregnated with the silica sol, gelling the silica sol to prepare a silica wet gel felt;
[0020] 4) surface modifying the silicon dioxide wet gel felt; and
[0021] 5) placing the surface-modified silica wet gel felt in a steam dryer and supplying steam to dry the felt,
[0022] The temperature inside the steam dryer is greater than 70°C.
[0023] (2) The present invention provides the method according to (1) above, wherein in step 5), the steam is supplied at a flow rate of 0.1 to 25 kg / h.
[0024] (3) The present invention provides the method according to (1) or (2) above, wherein the temperature inside the steam dryer is 80 to 250°C.
[0025] (4) The present invention provides the method according to any one of (1) to (3) above, wherein in step 5), steam is supplied for 30 minutes to 2 hours.
[0026] (5) The present invention provides a method according to any one of (1) to (4) above, wherein the felt substrate is a film, a sheet, a web, a fiber, a porous body, a foam, a nonwoven body, or a laminate of two or more thereof.
[0027] (6) The present invention provides the method according to any one of (1) to (5) above, wherein the silica precursor composition contains water glass.
[0028] (7) The present invention provides the method according to (6) above, wherein the gelation is performed using at least one acid catalyst selected from the group consisting of acetic acid, oxalic acid, nitric acid, sulfuric acid and hydrofluoric acid.
[0029] (8) The present invention provides a method according to (6) or (7) above, wherein the surface modification comprises immersing the silica wet gel felt in an aqueous acid mixture solution containing acetic acid and an acid catalyst, and surface-modifying the felt with an alkyldisiloxane compound.
[0030] (9) The present invention provides a method according to any one of (1) to (8) above, wherein the silica precursor composition is a mixture of a silicon-containing alkoxide compound, an alcohol and an acidic aqueous solution.
[0031] (10) The present invention provides a method according to the above (9), wherein the silicon-containing alkoxide compound is selected from at least one of the group consisting of tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra-sec-butyl orthosilicate, tetra-tert-butyl orthosilicate, tetrahexyl orthosilicate, tetracyclohexyl orthosilicate and tetradecyl orthosilicate.
[0032] Beneficial Effects
[0033] According to the present invention, a silica aerogel felt having high thermal insulation performance can be prepared by effectively drying in a short time. DETAILED DESCRIPTION
[0034] Hereinafter, the present invention will be described in detail to help understanding of the present invention.
[0035] It should be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It should also be understood that based on the inventors can appropriately define the meanings of words or terms to best explain the principles of the present invention, words or terms should be interpreted as having the meaning consistent with their meanings in the context of the relevant technology and technical ideas of the present invention.
[0036] The method for preparing a silica aerogel felt of the present invention comprises the following steps:
[0037] 1) preparing a silica sol containing a silica precursor composition; 2) impregnating a felt substrate with the silica sol; 3) gelling the silica sol while the felt substrate is impregnated with the silica sol to prepare a silica wet gel felt; 4) surface modifying the silica wet gel felt; and 5) placing the surface modified silica wet gel felt in a steam dryer and supplying steam to dry the felt, wherein the temperature inside the steam dryer is greater than 70°C.
[0038] Hereinafter, the present invention will be described in detail for each step.
[0039] Step 1)
[0040] Step 1) is a step of preparing a silica sol containing a silica precursor composition.
[0041] The silica precursor is a material that allows the aerogel to contain silica when prepared, and for example, water glass or a silicon-containing alkoxide compound may be used.
[0042] The water glass may be sodium silicate (Na2SiO3), which is an alkali metal silicate obtained by fusing silicon dioxide (SiO2) and an alkali, and when the silica precursor is water glass, the silica precursor composition may be a water glass solution in which distilled water is added to the water glass, mixed and diluted.
[0043] The water glass solution may contain 1 wt % to 13 wt % of silicon dioxide (SiO 2 ). When the water glass solution contains silicon dioxide in an amount below the above range, aerogel may not be properly formed, and when containing silicon dioxide in an amount above the above range, gelation may not function well or the specific surface area may be reduced.
[0044] Water glass solution is not necessarily used as a silicon dioxide precursor, and silicon-containing alkoxide compounds are also applicable. Specifically, the silicon dioxide precursor can be tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra-sec-butyl orthosilicate, tetra-tert-butyl orthosilicate, tetrahexyl orthosilicate, tetracyclohexyl orthosilicate, and tetradecyl orthosilicate. More specifically, the silicon dioxide precursor can be tetraethyl orthosilicate (TEOS).
[0045] When the silica precursor is a silicon-containing alkoxide compound, the silica precursor composition may be a mixture of the silicon-containing alkoxide compound, alcohol, and an acidic aqueous solution.
[0046] The alcohol may be a monohydric alcohol such as methanol, ethanol, isopropanol and butanol; or a polyhydric alcohol such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol and sorbitol, and any one of them or a mixture of two or more thereof may be used. Among them, when considering the miscibility with water and aerogel, the alcohol may be a monohydric alcohol having 1 to 6 carbon atoms, such as methanol, ethanol, isopropanol and butanol.
[0047] Those skilled in the art may use the alcohol as described above in an appropriate amount while promoting the surface modification reaction and taking into account the degree of hydrophobicity in the finally prepared aerogel.
[0048] The acid catalyst contained in the acidic aqueous solution may specifically include one or more inorganic acids such as nitric acid, hydrochloric acid, acetic acid, sulfuric acid, and hydrofluoric acid, which may be used to hydrate the silicon-containing alkoxide compound.
[0049] Regardless of the type of the silica precursor, the silica precursor may be used in an amount such that silica is contained in the silica sol in an amount of 1 wt % to 13 wt %, but is not limited thereto. When the amount of the silica precursor satisfies the above range, it is desirable in terms of ensuring excellent mechanical properties of the silica aerogel felt, particularly flexibility, and providing improved thermal insulation effects.
[0050] Step 2)
[0051] Step 2) is a step of impregnating the felt substrate with silica sol.
[0052] The term "impregnation" used herein may be performed by adding the catalyzed sol having fluidity into the substrate for felt, and may indicate that the catalyzed sol penetrates pores inside the substrate for felt.
[0053] The impregnation can be performed in a reaction vessel capable of accommodating the felt substrate, and can be performed by pouring the sol into the reaction vessel, or placing the felt substrate in a reaction vessel containing the sol for deposition. In this case, in order to improve the bonding between the felt substrate and the sol, the felt substrate can be slightly pressed down for sufficient impregnation. Thereafter, the felt substrate is pressed to a predetermined thickness under a constant pressure to remove the remaining sol, so that the drying time can be reduced.
[0054] According to one embodiment of the present invention, the felt substrate may be a film, a sheet, a net, a fiber, a porous body, a foam, a nonwoven body, or a laminate of two or more layers thereof. In addition, surface roughness may be formed or patterned on its surface depending on its use. Specifically, the felt substrate may be a fiber capable of further improving thermal insulation performance by including a space or void in which the silica aerogel is easily inserted into the felt substrate, and a felt substrate having a low thermal conductivity may be used.
[0055] Specifically, the felt substrate can be polyamide, polybenzimidazole, polyaramid, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (such as polyethylene, polypropylene or their copolymers), cellulose, carbon, cotton, wool, hemp, nonwoven fabric, glass fiber or ceramic wool, but is not limited thereto.
[0056] Step 3)
[0057] Step 3) is a step of gelling the silica sol in a state where the felt substrate is impregnated with the silica sol to prepare a silica wet gel felt;
[0058] In the present invention, gelation can be the formation of a network structure by a silica precursor material, and the network structure can be a planar mesh structure in which specific polygons having one or more types of atomic arrangements are connected to each other, or a structure in which specific polyhedrons share their vertices, edges, faces, etc. with each other to form a three-dimensional skeleton structure.
[0059] When the silicon dioxide precursor is water glass, gelation can be performed by an acid catalyst. As the acid catalyst, any one or more of an organic acid and an inorganic acid that do not have chlorine in the molecular structure of the compound can be used. For example, the acid catalyst can be one or more selected from the group consisting of acetic acid, oxalic acid, nitric acid, sulfuric acid and hydrofluoric acid, and specifically can be acetic acid, nitric acid, sulfuric acid or a mixture of two or more thereof.
[0060] The acid catalyst may be contained in an amount such that the silica sol has a pH of 3 to 10. When the pH of the silica sol is outside the above range, gelation may not proceed well, or gelation may be too fast or too slow, which may reduce processability.
[0061] When the silica precursor is a silicon-containing alkoxide compound, gelation can be performed by an alkali catalyst. Specifically, the alkali catalyst is used to promote gelation by increasing the pH of the silica sol.
[0062] The base catalyst may be an inorganic base such as sodium hydroxide and potassium hydroxide, or an organic base such as ammonium hydroxide, but is not limited thereto.
[0063] Specifically, the organic base can be ammonium hydroxide (NH4OH), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, N-methyldiethanolamine, dimethylaminoethanol, diethylaminoethanol, nitrotriethanol, 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine or dibutanolamine, and among the above, any one thereof or a mixture of two or more thereof can be used.
[0064] More specifically, in the present invention, the base may be ammonium hydroxide (NH4OH) or sodium hydroxide (NaOH).
[0065] The alkali catalyst may be contained in an amount such that the silica sol has a pH of 3 to 10. When the pH of the silica sol is outside the above range, gelation may not work well, or gelation may become too slow, which may reduce processability. In addition, when added in a solid phase, the alkali may precipitate, and it is preferred that the alkali is added in the form of a solution diluted with an alcohol (polar organic solvent).
[0066] Additional process: aging process
[0067] In the present invention, the silica wet gel felt prepared after gelation in step 3) can be further aged. Aging is a process in which the silica wet gel felt is placed at an appropriate temperature to complete chemical changes, and can make the formed network structure stronger, so that the silica aerogel felt has greater mechanical stability.
[0068] Aging should be performed within an appropriate temperature range to optimally enhance the pore structure, and the aging of the present invention can be performed by maintaining the silica wet gel felt at a temperature of 30 to 70° C. for 3 to 50 hours. When the aging temperature is within the above range, productivity can be obtained by aging at an appropriate level, and loss caused by evaporation of the organic solvent can be prevented. In addition, the aging time within the above range represents a range that can satisfy the thermal conductivity and hydrophobicity, and can be preferably 6 hours to 48 hours, more preferably 18 hours to 48 hours.
[0069] In addition, according to an embodiment of the present invention, aging can be carried out in a separate reaction vessel after recovering the silica wet gel felt in which gelation is completed, or can be carried out inside the reaction vessel in which gelation is carried out, and can preferably be carried out in the above-mentioned reaction vessel in which gelation is carried out, so as to facilitate process efficiency and equipment simplification.
[0070] Step 4)
[0071] Step 4) is a step of surface-modifying the silica wet gel felt.
[0072] When the hydrophilic functional groups present on the surface of the aerogel are replaced by hydrophobic functional groups, the shrinkage of the pores caused by the surface tension of the solvent during the drying process of the aerogel can be minimized by the repulsive force between the hydrophobic functional groups. The dried aerogel maintains low thermal conductivity immediately after drying, but the hydroxyl functional groups present on the surface of the aerogel (for example, when the aerogel is a silica aerogel) absorb water in the air, resulting in a gradual increase in thermal conductivity. Therefore, in order to maintain low thermal conductivity, it is necessary to modify the surface of the aerogel to be hydrophobic.
[0073] The surface modification of the present invention can be carried out using a compound that hydrophobizes the surface of the wet gel without limitation.
[0074] For example, the compound may be a silane compound, a siloxane compound, a silanol compound, a silazane compound or a combination thereof.
[0075] Specifically, the compound can be a silane compound, including trimethylchlorosilane (TMCS), dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane, trimethylethoxysilane, vinyltrimethoxysilane, ethyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, tetraethoxysilane, dimethyldichlorosilane, 3-aminopropyltriethoxysilane; siloxane compounds, including polydimethylsiloxane, polydiethylsiloxane or octamethylcyclotetrasiloxane ; Silanol compounds, including trimethylsilanol, triethylsilanol, triphenylsilanol and tert-butyldimethylsilanol; silazane compounds, including 1,2-diethyldisilazane, 1,1,2,2-tetramethyldisilazane, 1,1,3,3-tetramethyldisilazane, 1,1,1,2,2,2-hexamethyldisilazane (HMDS), 1,1,2,2-tetraethyldisilazane or 1,2-diisopropyldisilazane; or a combination thereof, and specifically may be hexamethyldisilazane.
[0076] For example, when a silicon-containing alkoxide compound is used as a silica precursor, the surface modifier can be used as a solution phase diluted in an organic solvent, and the organic solvent can be an alcohol (organic solvent), and in this case, the surface modifier can be diluted in an amount of 1 to 15 volume % relative to the total volume of the diluted solution.
[0077] In addition, the surface modifier can be added in an amount of 0.01 to 10% by volume relative to the silica wet gel felt. Within the above range, the amount of the surface modifier is sufficient, and therefore, the surface modification reactivity can be excellent, and the surface modification can also be easily achieved, and this can inhibit the condensation reaction of the silanol group that is not surface-modified during drying to allow the silica aerogel felt as the final product to have an even greater porosity.
[0078] Step 4) may be adding the surface modifier at a temperature of 50 to 90° C., preferably 50 to 80° C. for 1 to 24 hours.
[0079] For example, when water glass is used as the silica precursor, a process of additionally adding toluene to the wet gel may be performed before the surface modification in step 4). In the additional addition of toluene, toluene may be added after the acid mixture aqueous solution is added to the wet gel but before the alkyldisiloxane compound is added, or may be added together with the acid mixture aqueous solution and the alkyldisiloxane compound.
[0080] In the additional addition of toluene in step 4), toluene may be contained in the hydrophobic organic solution layer. When sulfuric acid is used as an acid catalyst, in the case of adding toluene, p-toluenesulfonic acid is formed by the reaction of sulfuric acid and toluene, and p-toluenesulfonic acid acts as a catalyst for the activation of the surface modification reaction by the alkyldisiloxane compound, showing a very excellent surface modification reaction rate.
[0081] The concentration of the acid catalyst after step 4) (w / w%) represents the concentration of the acid catalyst contained in the acid mixture aqueous solution layer after step 4), and can be expressed by the following equation 2. The concentration of the acid catalyst can be calculated by measuring the weight of water in the acid mixture aqueous solution layer after step 4), and then measuring the weight of the acid catalyst in the acid mixture aqueous solution layer by gas chromatography (GC).
[0082] [Equation 2]
[0083] Acid catalyst concentration (w / w%) = weight of acid catalyst / (weight of acid catalyst + total weight of water in the acid mixture aqueous solution layer) × 100
[0084] As described above, when the immersion process in the acid mixture aqueous solution is completed, the acid concentration inside the wet gel and the acid concentration outside the wet gel reach equilibrium, and therefore, when the acid concentration of the acid mixture aqueous solution layer is measured after immersion, the acid concentration inside the wet gel can be indicated, thereby determining the acid concentration involved in the surface modification.
[0085] After step 4), the water contained in the acid mixture aqueous solution layer may be water contained in the acetic acid aqueous solution and the acid catalyst, water contained in the wet gel, and water remaining after step 4) from the water resulting from the hydrophilic-hydrophobicization reaction of the wet gel, and the total weight thereof may be the total weight of the water in the acid mixture aqueous solution layer.
[0086] Step 4) can be carried out by immersing the wet gel in an aqueous solution of the acid mixture and then sequentially surface-modifying the resulting product with an alkyl disiloxane compound.
[0087] In the method for preparing a silica aerogel felt according to an embodiment of the present invention, when the wet gel is immersed in the acid mixture aqueous solution in step 4), an acid mixture aqueous solution containing acetic acid and an acid catalyst is used to ensure that the acetic acid meets a certain volume relative to the wet gel, and the acetic acid concentration meets the above value after step 4), and for the wet gel, especially the hydrogel prepared using the water glass solution. This can allow for rapid, sufficient and effective surface modification.
[0088] The alkyldisiloxane-based compound may be added in a volume ratio of 1 to 3 times, specifically 1 to 2.5 times, more specifically 1 to 2 times, relative to the volume of the wet gel.
[0089] The alkyldisiloxanyl compound needs to be added in a volume of at least 1 times relative to the volume of the wet gel to modify the wet gel and perform solvent exchange on the wet gel, and when the amount of the alkyldisiloxanyl compound is increased, a larger equipment is required, therefore, the alkyldisiloxanyl compound may be added within the above range relative to the volume of the wet gel.
[0090] The alkyl disiloxane compound may be a hexaalkyl disiloxane compound, specifically hexa(C 1-8 alkyl) disiloxane, more specifically hexamethyldisiloxane.
[0091] The surface modification reaction may be performed at a temperature of 25° C. to 95° C. In addition, a stirring process may be performed during the process of immersing the wet gel in the acid mixture aqueous solution and during the process of surface-modifying the wet gel with the alkoxydisiloxane compound.
[0092] In this case, stirring is not particularly limited, but may be performed at a speed of, for example, 50 rpm to 700 rpm.
[0093] Furthermore, step 4) according to an embodiment of the present invention may be performed for 2 to 24 hours, and may preferably be performed for 4 to 22 hours or 8 to 20 hours, in order to facilitate improving the economic efficiency of the process and maintaining the surface modification effect at an excellent level.
[0094] In the preparation method according to an embodiment of the present invention, when step 4) is performed by a method in which the process of immersing the wet gel in the acid mixture aqueous solution and the process of surface modification with an alkyldisiloxane compound are sequentially performed, the process of immersing the wet gel in the acid mixture aqueous solution can be performed for 30 minutes to 4 hours, specifically 30 minutes to 3 hours, more specifically 1 hour to 3 hours, and the method of surface modification with an alkyldisiloxane compound can be performed for 1.5 hours to 20 hours, specifically 3 hours to 19 hours, more specifically 6 hours to 18 hours.
[0095] In the present invention, when the silica precursor is water glass, a surface modifier containing an organic silane compound can be used for surface modification, and when the silica precursor is a silicon-containing alkoxide compound, a surface modifier containing a polar solvent and an organic silane compound can be used for surface modification.
[0096] As the polar solvent, methanol, ethanol or isopropanol can be used. As the organosilane compound, trimethylchlorosilane (TMCS), hexamethyldisilazane (HMDS), or methyltrimethoxysilane (MTMS), trimethylethoxysilane (TMES), ethyltriethoxysilane (ETES) or phenyltriethoxysilane (PTES) can be used, preferably trimethylethoxysilane or hexamethyldisilazane.
[0097] In the case of a polar solvent, the surface modifier is preferably mixed at a volume ratio of 0.5 to 10.0 relative to the wet gel, in the case of an organosilane compound, the surface modifier is mixed at a volume ratio of 0.1 to 10.0 relative to the wet gel, and the surface modifier containing the organosilane compound and the polar solvent may be mixed at a volume ratio of 0.5 to 10.0 relative to the wet gel. When the volume ratio of the organosilane compound to the wet gel is less than 0.1, the reaction takes too long and the surface modification efficiency may be reduced, and when the volume ratio of the organosilane compound is greater than 10.0, the cost increases and the unreacted surface modifier may cause shrinkage during drying.
[0098] The organosilane compound and the polar solvent may be mixed in the above volume ratio, and the mixed surface modifier may contain the organosilane compound in an amount of 10 volume % to 60 volume % relative to the total volume of the surface modifier. The amount of the organosilane compound in the surface modifier may affect the degree of hydrophobicity and thermal conductivity, and the degree of hydrophobicity and thermal conductivity may be improved with a higher amount, but when the amount is greater than 60 volume %, the surface modification efficiency is not additionally increased, but the amount of waste organosilane compound increases, so the amount needs to be appropriately adjusted within the above range.
[0099] In the preparation method according to an embodiment of the present invention, the surface modification process can be carried out for 10 hours to 50 hours, preferably 15 hours to 50 hours, more preferably 18 hours to 48 hours, and even more preferably 24 hours to 48 hours. The treatment time of the surface modification as described above is to obtain an appropriate degree of hydrophobicity, and the treatment can preferably be carried out within the above range to achieve a thermal conductivity and hydrophobicity of the final aerogel felt higher than a certain level.
[0100] The above-mentioned surface modification can be carried out in a separate reaction vessel after recovering the silica wet gel-fiber composite material in which gelation or aging is completed, or can be carried out inside the reaction vessel in which gelation or aging is carried out, and for the benefits of process efficiency and equipment simplification, aging and surface modification can preferably be carried out in the above-mentioned reaction vessel in which gelation or aging is carried out.
[0101] After surface modification, a hydrophobic wet gel-fiber composite material can be obtained.
[0102] Step 5)
[0103] Step 5) is a step of placing the surface-modified silica wet gel felt in a steam dryer and supplying steam to dry the felt. In this case, the temperature in the steam dryer is greater than 70°C.
[0104] The atmospheric pressure drying method does not require the high pressure reaction conditions or specific high pressure equipment required for supercritical drying, so it is simple and economical, but it can significantly cause the collapse of the internal pore structure of the gel compared to supercritical drying, resulting in a sharp decrease in the thermal insulation performance due to the evaporation of water or organic solvents at high temperatures. In addition, the atmospheric pressure drying process brings safety issues, such as the risk of oil mist explosion.
[0105] Meanwhile, supercritical drying is performed under high pressure and thus requires high costs, and vacuum drying may cause deterioration of physical properties of the aerogel felt due to a drop in internal temperature during drying.
[0106] In the present invention, steam drying is adopted as a drying method for the silica wet gel felt, thereby suppressing the shrinkage of the aerogel occurring during drying to improve thermal insulation, shortening the time required for drying, and simplifying the required equipment and conditions to improve the economic efficiency of drying. In addition, steam drying does not have any problems caused when using other drying methods as described above.
[0107] In the present invention, a steam dryer can be used regardless of its form or device name, but in order to fully meet the purpose of drying the silica wet gel felt in the present invention, the steam dryer needs to be used to increase and maintain the temperature to prevent steam from condensing in the steam dryer, and needs to withstand steam pressure and weak negative pressure.
[0108] In the present invention, steam may be supplied at a flow rate of 0.1 to 25 kg / h, and specifically, the flow rate may be 5 to 25 kg / h or 15 to 25 kg / h.
[0109] When the supply flow rate of steam is within the above range, the heat transfer effect from the steam is excellent, the drying efficiency is excellent, the physical properties of the aerogel felt are improved, the reduction in economic efficiency due to excessive use of steam is prevented, and the condensation reaction due to residual water is induced, resulting in no deterioration of the physical properties of the aerogel.
[0110] In the present invention, the temperature inside the steam dryer is greater than 70° C. More specifically, the temperature may be 80 to 250° C., 80 to 200° C., and 80 to 120° C.
[0111] When the temperature inside the steam dryer is within the above range, steam condensation caused by excessively low temperature can be prevented from hindering heat transfer, the difference in internal and external physical properties of the aerogel felt caused by high temperature caused by ambient heat can be prevented, and the difficult-to-achieve energy cost reduction can be solved.
[0112] In the present invention, any specific method is not limited as long as steam is applied to transfer heat to the silica wet gel felt. For example, the direction in which steam is sprayed in the steam dryer and the speed or total amount of steam spraying are also not limited.
[0113] In the present invention, the drying time for applying steam may vary according to the size of the silica wet gel mat, but may be, for example, 30 minutes to 2 hours.
[0114] In particular, when a water glass solution is used as a silica precursor in preparing the silica sol, the drying method of the present invention can further maximize its effect.
[0115] When water glass is used as a silica precursor, the surface modifier remains as a solvent in the silica wet gel after the surface modification is completed, and the surface modifier is hydrophobic and therefore does not mix with water, and therefore, the recovered surface modifier (solvent) and the condensed steam are easily separated even after drying, thereby providing the benefit of easily recovering the expensive and reusable surface modifier to improve economic benefits, and recovering the silica aerogel felt as the final product.
[0116] Meanwhile, the method for preparing aerogel felt according to an embodiment of the present invention may further include a washing step before the drying step. Washing is to obtain a high-purity hydrophobic aerogel by removing impurities and residual ammonia generated during the reaction, and can be performed by a dilution method or an exchange method using an organic solvent.
[0117] Furthermore, according to an embodiment of the present invention, the method for preparing an aerogel felt may specifically be a method for preparing a silica aerogel felt, and the aerogel felt produced by the preparation method may be a silica aerogel felt.
[0118] Example
[0119] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the following Examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0120] Example 1
[0121] 33.8 g of water glass was diluted in 108.1 g of water to prepare a water glass solution, and 7.8 g of acetic acid (97%) was added to prepare a silica sol. The glass fiber was impregnated with the silica sol and left for 10 minutes to obtain a glass fiber composite material impregnated with a wet gel.
[0122] 140 g of acetic acid (≥-97%) and 15 g of nitric acid aqueous solution (70%) (w / w%) were mixed to prepare an acid mixture aqueous solution, which was then poured onto the glass fiber impregnated with the wet gel and immersed in an oven at 60° C. for 2 hours at a constant temperature, and then 160 g of hexamethyldisiloxane (HMDSO) was added and a surface modification reaction was performed in an oven at 75° C. for 16 hours at a constant temperature. In this case, the acetic acid in the acid mixture aqueous solution was used in an amount of 1 L relative to the volume of 1 L of the wet gel, and the hexamethyldisiloxane was used in an amount of 1.5 L relative to the volume of 1 L of the wet gel.
[0123] Thereafter, the surface-modified silica wet gel felt was placed in a steam dryer and continuously injected with steam for steam drying (90° C. in the steam dryer, a steam flow rate of 20 kg / h, for 30 minutes).
[0124] Example 2
[0125] A hydrochloric acid solution (concentration = 0.15 wt %) diluted in water was added to a mixed solution prepared by mixing tetraethyl orthosilicate (TEOS) and aqueous ethanol in a weight ratio of 3:1 so that the mixed solution had a pH of 1, and then further mixed with aqueous ethanol to prepare a silica sol (silicon dioxide content: 4 wt %).
[0126] Thereafter, 0.5 volume % of an alkali catalyst was added to the silica sol to initiate a gelation reaction, and glass fibers were deposited to prepare a silica wet gel composite. A surface modifier solution prepared by mixing hexamethyldisilazane and ethanol in a volume ratio of 1:19 was added in an amount of 90 volume % relative to the wet gel, and the surface was modified at 70°C for 4 hours to prepare a hydrophobic silica wet gel felt.
[0127] Thereafter, the surface-modified silica wet gel felt was placed in a steam dryer and continuously injected with steam for steam drying (90° C. in the steam dryer, a steam flow rate of 20 kg / h, for 30 minutes).
[0128] Example 3
[0129] A silica aerogel felt was prepared in the same manner as in Example 1, except that the drying conditions were set to an internal temperature of 150° C., a steam flow rate of 20 kg / h, and a time of 30 minutes in a steam dryer.
[0130] Example 4
[0131] A silica aerogel felt was prepared in the same manner as in Example 1, except that the drying conditions were set to an internal temperature of 90° C. in a steam dryer, a steam flow rate of 25 kg / h, and a time of 30 minutes.
[0132] Example 5
[0133] A silica aerogel felt was prepared in the same manner as in Example 1, except that the drying conditions were set to an internal temperature of 90° C. in a steam dryer, a steam flow rate of 20 kg / h, and a time of 60 minutes.
[0134] Example 6
[0135] A silica aerogel felt was prepared in the same manner as in Example 1, except that the drying conditions were set to an internal temperature of 200° C., a steam flow rate of 20 kg / h, and a time of 30 minutes in a steam dryer.
[0136] Example 7
[0137] A silica aerogel felt was prepared in the same manner as in Example 1, except that the drying conditions were set to an internal temperature of 90° C. in a steam dryer, a steam flow rate of 10 kg / h, and a time of 30 minutes.
[0138] Comparative Example 1
[0139] The silica wet gel felt prepared in the same manner as in Example 1 was placed in a convection oven and dried at 150° C. for 90 minutes under normal pressure to completely remove the solvent and moisture, thereby preparing a silica aerogel felt.
[0140] Comparative Example 2
[0141] The silica wet gel felt prepared in the same manner as in Example 1 was vacuum dried in a vacuum oven at 150° C. for 90 minutes to prepare a silica aerogel felt.
[0142] Comparative Example 3
[0143] The silica wet gel felt prepared in the same manner as in Example 1 was placed in a supercritical extractor, carbon dioxide was injected, the temperature in the extractor was raised to 50°C for 1 hour, and supercritical drying was performed at 50°C and 100 bar to prepare a silica aerogel felt.
[0144] Comparative Example 4
[0145] A silica aerogel felt was prepared in the same manner as in Example 1, except that the drying conditions were set to an internal temperature of 70° C., a steam flow rate of 20 kg / h, and a time of 30 minutes in a steam dryer.
[0146] Experimental Example 1
[0147] Five samples with a size of 15 cm×15 cm were prepared from each of the silica aerogel felts prepared in the Examples and Comparative Examples, and the thermal conductivity of the samples was measured at room temperature (23±5° C.) using a HFM436 Lambda device from NETZSCH.
[0148] For thermal conductivity, the heat flow of the sample located between the hot plate and the cold plate is measured by a heat flow sensor in the device, and based on this measurement, a calibration factor (N) can be obtained from a reference material with a known thermal conductivity value, and a calculated value of thermal conductivity can be obtained from this N value and the measured heat flow value of the sample. In this method, the thickness of the sample is also obtained as a measured value.
[0149] [Table 1]
[0150] Thermal conductivity (mW / mK) Thickness(mm) Drying time (minutes) Example 1 17.5 10.1 30 Example 2 17.8 10.3 30 Example 3 18.0 10.2 30 Example 4 17.4 10.0 30 Example 5 17.7 10.2 60 Example 6 17.9 10.3 30 Example 7 17.8 10.2 30 Comparative Example 1 18.1 10.1 90 Comparative Example 2 21.9 9.1 90 Comparative Example 3 17.4 10.1 240 Comparative Example 4 25.0 9.5 30
[0151] As shown in Table 1, in Examples 1 to 7 in which drying was performed according to the present invention, it can be seen that drying was performed without shrinkage and the thermal insulation performance was also excellent. In addition, the drying time required to obtain the above-mentioned performance was also very short. At the same time, Comparative Examples 1 and 2 took longer to complete drying than in the Examples, indicating that drying took longer than steam drying. In Comparative Example 3, supercritical drying was performed, and it can be seen that the drying time needed to be 8 times longer to obtain physical properties similar to those in the Examples.
[0152] In addition, it can be seen that Comparative Example 4 shows shrinkage during drying due to its thinner thickness and reduced thermal insulation performance compared to the Examples. This indicates that the steam drying temperature is low, so the steam condenses on the wall and felt surface inside the steam dryer, making the steam unable to be used as a heat carrier, and water droplets are formed on the felt surface, slowing down drying or causing shrinkage.
Claims
1. A method for preparing a silica aerogel felt, the method comprising the following steps: 1) preparing a silica sol containing a silica precursor composition; 2) impregnating a felt substrate with the silica sol; 3) while the felt substrate is impregnated with the silica sol, gelling the silica sol to prepare a silica wet gel felt; 4) surface modifying the silicon dioxide wet gel felt; and 5) placing the surface-modified silica wet gel felt in a steam dryer and supplying steam to dry the felt, The temperature inside the steam dryer is greater than 70°C.
2. The method of claim 1, wherein in step 5), the steam is supplied at a flow rate of 0.1 kg / h to 25 kg / h.
3. The method of claim 1, wherein the temperature inside the steam dryer is 80 to 250°C.
4. The method of claim 1, wherein in step 5), the steam is supplied for 30 minutes to 2 hours.
5. The method of claim 1, wherein the felt substrate is a film, a sheet, a web, a fiber, a porous body, a foam, a nonwoven body, or a laminate of two or more thereof.
6. The method of claim 1, wherein the silica precursor composition comprises water glass.
7. The method of claim 6, wherein the gelling is performed using at least one acid catalyst selected from the group consisting of acetic acid, oxalic acid, nitric acid, sulfuric acid, and hydrofluoric acid.
8. The method of claim 6, wherein the surface modification comprises immersing the silicon dioxide wet gel felt in an acid mixture aqueous solution containing acetic acid and an acid catalyst, and surface-modifying the felt with an alkyl disiloxane compound.
9. The method of claim 1, wherein the silicon dioxide precursor composition is a mixture of a silicon-containing alkoxide compound, an alcohol and an acidic aqueous solution.
10. The method of claim 9, wherein the silicon-containing alkoxide compound is at least one selected from the group consisting of tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra-sec-butyl orthosilicate, tetra-tert-butyl orthosilicate, tetrahexyl orthosilicate, tetracyclohexyl orthosilicate and tetra(dodecyl)orthosilicate.
Citation Information
Patent Citations
Industrial facility information sharing system using augmented reality
KR1020220107778A